(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2007)
The objective of this study was the investigation of behaviors classified as Body Dysmorphic Disorder and the contingencies of its development and maintenance. A descriptive exploratory study was done using the interviews with seven patients and their families to raise some hypothesis based on the theoretical principles of Radical Behaviorism. Checking the supposed defect in the mirror; camouflage rituals; social avoidance; depressive behaviors; obsessive-compulsive behaviors and delusions was found. Their life history indicated a coercive education, great emphasis on beauty, restrictive social interactions, accidents and commentary on parts of the body by others and many plastic surgeries. Under the specific stimulus control like his own alleged defect and the regard of others, many participants’ classes of behavior had the function of escape/avoidance and was negatively reinforced, preventing participants from exposing themselves to others and being criticized. Some behaviors were described as experiential avoidance, as they had the function of avoiding their private aversive condition bringing some major consequences in social, personal and occupational areas.